2012
DOI: 10.1111/j.1365-2915.2011.00997.x
|View full text |Cite
|
Sign up to set email alerts
|

Housing and dustbathing effects on northern fowl mites (Ornithonyssus sylviarum) and chicken body lice (Menacanthus stramineus) on hens

Abstract: Hen housing (cage or cage-free) did not impact overall abundances of northern fowl mites, Ornithonyssus sylviarum (Canestrini & Fanzago) (Acari: Macronyssidae), or chicken body lice, Menacanthus stramineus (Nitzsch) (Phthiraptera: Menoponidae). Cage-free hens received a dustbox with sand plus diatomaceous earth (DE), kaolin clay or sulphur. Weekly use varied from none to 100% of hens; 73% of hens used the dustbox at least once. Ectoparasite populations on dustbathing hens (users) were compared with those on no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…A recent study showed that hen dustbathing in natural dust materials (particularly kaolin) can suppress ectoparasites (Martin and Mullens, 2012) that offers opportunities for reducing the use of medication. Trained conspecifics are also important for facilitating the consumption of new feed pellets (Oostindjer et al, 2011) or the learning of self-feeding devices (Noble et al, 2012), but further studies are required to quantify the consequences on production efficiency.…”
Section: Exploiting Animal Adaptive Capacitiesmentioning
confidence: 99%
“…A recent study showed that hen dustbathing in natural dust materials (particularly kaolin) can suppress ectoparasites (Martin and Mullens, 2012) that offers opportunities for reducing the use of medication. Trained conspecifics are also important for facilitating the consumption of new feed pellets (Oostindjer et al, 2011) or the learning of self-feeding devices (Noble et al, 2012), but further studies are required to quantify the consequences on production efficiency.…”
Section: Exploiting Animal Adaptive Capacitiesmentioning
confidence: 99%
“…Hoffman and Hogan (1967) demonstrated that sand did not affect lice populations when it was available for dustbathing, although they did not observe whether the hens actually used the dustbox. Martin and Mullens (2012) showed that hens that used dustboxes filled with sand and inorganic inert dusts like kaolin or diatomaceous earth, or with sand and sulphur, had reduced northern fowl mite and chicken body louse populations compared to hens that did not use the dustboxes. Kilpinen and Steenberg (2009) and Martin and Mullens (2012) suggested that, due to their fine size and oil absorption capacity, inorganic inert dusts like kaolin clay and diatomaceous earth might abrade the cuticle, or more likely absorb the lipid on the cuticle leading to desiccation of the ectoparasites.…”
Section: Measurementioning
confidence: 98%
“…Martin and Mullens (2012) showed that hens that used dustboxes filled with sand and inorganic inert dusts like kaolin or diatomaceous earth, or with sand and sulphur, had reduced northern fowl mite and chicken body louse populations compared to hens that did not use the dustboxes. Kilpinen and Steenberg (2009) and Martin and Mullens (2012) suggested that, due to their fine size and oil absorption capacity, inorganic inert dusts like kaolin clay and diatomaceous earth might abrade the cuticle, or more likely absorb the lipid on the cuticle leading to desiccation of the ectoparasites. Perhaps either the size or nature of sand grains causes sand to be ineffective for in abrading or absorbing oil from the mite cuticle.…”
Section: Measurementioning
confidence: 98%
See 2 more Smart Citations